ANALISIS SIFAT MEKANIK KOMPOSIT SERAT BAMBU TALI SEBAGAI MULTILAYERED ARMOR SYSTEM - Ramin, Rosihan; Sofyan , Bondan Tiara; Hafizah, Mas Ayu Elita (POLITALA PRESS, 2023)
Natural fiber composites are an alternative Multilayered Armor System (MAS) material. One of the most common natural fibers used as MAS is a fiber made from bamboo rope. Bamboo fiber composites have a low density and a low manufacturing cost. However, in terms of mechanical properties, bamboo fiber composites have different characteristics. In this research, the mechanical properties of the bamboo rope fiber composite, which has an orientation of 0°/90°, will be analyzed. The composite materials used are bamboo rope fiber as a reinforcement and epoxy as the fiber binding matrix. From the mechanical tests performed, it was found that the average tensile strength of the bamboo rope fiber composite was 109.86 MPa. The bending strength is 95.32 MPa, and the shear strength is 34.11 MPa.